The caregiving burden of older people with functional deficits and associated factors on Malaysian family caregivers - Abdul Wahab, Patimah; Abdul Talib, Nurul Afiah; Nik Mohd Hatta, Nik Noor Kaussar; Saidi, Sanisah; Abdul Mulud, Zamzaliza; Abdul Wahab, Muhammad Nubli; Pairoh, Hasanah (Penerbit Universiti Sains Malaysia, 2024)
Background: Providing care to older people can be an extremely complex task, given their increased functional deficits, which may lead to family caregivers experiencing burnout and a deteriorated health status. This study investigated the caregiving burden of older people with functional deficits on family caregivers and associated factors. Methods: This cross-sectional study was conducted on family caregivers of older people with functional deficits living in FELDA schemes in Pahang, Malaysia. A self-administered questionnaire was used to collect data, which included the sociodemographical profile, health status and caregiving demands factors. The caregiving burden was assessed using the Malay version of the Zarit Burden Interview (ZBI). Multiple linear regression was used to assess the factors associated with burden. Results: A total of 271 family caregivers completed the questionnaire. Their mean age was 45.8 (SD 0.9) years old. The mean score for caregiving burden was 18.5 (SD 13.6). Caregivers’ gender (3.5 [95% CI: 0.2, 6.8]; P = 0.037), older people with chronic disease (9.6 [95% CI: 2.4, 16.9]; P = 0.010) and the functional independence of older people (–1.1 [95% CI: –1.6, –0.6]; P < 0.001) were predictors of family caregiving burden. Conclusion: The caregiving burden among family caregivers was mild and influenced mainly by care recipients’ health status. A proper assessment should be conducted and relevant health education provided to prepare family caregivers to care for their family members before discharge from the hospital.